When the Value of Cooperating Scales: Collective Intelligence, Information Processing, and the Leadership Meta-Capability - Hazy, James K. (Frontiers in Human Dynamics, 2021)
This article explores the nexus where purposeful individual-driven collective action, what is called organizational leadership, interacts with collective intelligence and agency. Based on recent numerical models from complex network theory and empirical studies of collective dynamics in social biology, it describes how intelligent collective agency forms around three order parameters: expectancy alignment, instrumental momentum inside the collective, and generalized trustworthiness among its members. When the value of one or more of these scaling metrics becomes dynamically stable, fractal structures in the collective provide useful information to individuals that informs their choices during interactions including leadership activities. The theory contributes fourteen testable assertions that if supported empirically suggest fruitful ways that new information technology applications could enhance organizational effectiveness.